Visible Light-Induced Aerobic Amine Oxidation to Imine in Aqueous Salt Solutions: Saline and Sustainable - Kare, Varsha S.; Patil, Yash; Tiwari, Shraeddha S. (Sustainability & Circularity NOW, 2026)
The selective photooxidation of C–N bond in amines is a process of prime importance but remains challenging. Herein, we report the application of aqueous salt solutions as reaction media for the selective synthesis of imine from benzylamine. Oxidation of benzylamine as the representative amine using aqueous salt solutions as reaction media resulted in much higher conversion (~99%) as compared to that obtained in conventionally used solvents such as acetonitrile. Control experiments indicate that the reaction outcome is relatively unaffected by the type of ions used – indicating limited contribution from ion-specific pathways and implicating synergistic contributions of various species at the catalytic interface. Gram-scale synthesis and reusability of the reaction system for at least five reaction cycles indicates good catalyst stability. This is the first report using aqueous salt solutions for oxidation of benzylamine using cooperative TiO2–TEMPO photocatalyst. The approach has the potential to be extended to other photocatalytic oxidations with promising results.
Keywords: Photocatalysis; Amine oxidation; Aqueous solution; Interfacial effect; Heterogeneous catalysis